What can challenging reproductive contexts tell us about the rat’s maternal behavior? - Agrati, Daniella; Uriarte, Natalia (Frontiers in Behavioral Neuroscience, 2023)
Maternal behavior in mammals encompasses a complex repertoire of activities that ensure the survival of the offspring and shape their neural and behavioral development. The laboratory rat has been employed as a classic model for investigating maternal behavior, and recently with the use of advanced techniques, the knowledge of its neural basis has been expanded significantly. However, the standard laboratory testing conditions in which rats take care of a single litter impose constraints on the study of maternal flexibility. Interestingly, the reproductive characteristics of this species, including the existence of a fertile postpartum estrus, allow us to study maternal behavior in more complex and ethologically relevant contexts, even in laboratory settings. Here we review how maternal and sexual motivations interact during the postpartum estrus, shaping the behavioral response of females according to the presence of the pups and males. Next, we describe how impregnation during the postpartum estrus creates a new reproductive context in which mothers simultaneously care for two successive litters, adapting their responses to different behavioral and physiological demands of pups. These findings illustrate the behavioral adaptability of maternal rats to pups' needs and the presence of other reinforcers, as well as its dependence on the context. In our view, future perspectives in the field, by incorporating the use of cutting-edge techniques, should analyze maternal flexibility and its neural substrates in models that incorporate complex and challenging contexts. This approach would allow a more comprehensive understanding of brain circuits involved in the adaptive and flexible nature of parenting.